13,915 reasons for equity in sexual offences legislation: A national school-based survey in South Africa - Ho-Foster Ari; Andersson Neil (BMC, 2008)
Abstract Objective Prior to 2007, forced sex with male children in South Africa did not count as rape but as "indecent assault", a much less serious offence. This study sought to document prevalence of male sexual violence among school-going youth. Design A facilitated self-administered questionnaire in nine of the 11 official languages in a stratified (province/metro/urban/rural) last stage random national sample. Setting Teams visited 5162 classes in 1191 schools, in October and November 2002. Participants A total of 269,705 learners aged 10-19 years in grades 6-11. Of these, 126,696 were male. Main outcome measures Schoolchildren answered questions about exposure in the last year to insults, beating, unwanted touching and forced sex. They indicated the sex of the perpetrator, and whether this was a family member, a fellow schoolchild, a teacher or another adult. Respondents also gave the age when they first suffered forced sex and when they first had consensual sex. Results Some 9% (weighted value based on 13915/127097) of male respondents aged 11-19 years reported forced sex in the last year. Of those aged 18 years at the time of the survey, 44% (weighted value of 5385/11450) said they had been forced to have sex in their lives and 50% reported consensual sex. Perpetrators were most frequently an adult not from their own family, followed closely in frequency by other schoolchildren. Some 32% said the perpetrator was male, 41% said she was female and 27% said they had been forced to have sex by both male and female perpetrators. Male abuse of schoolboys was more common in rural areas while female perpetration was more an urban phenomenon. Conclusion This study uncovers endemic sexual abuse of male children that was suspected but hitherto only poorly documented. Legal recognition of the criminality of rape of male children is a first step. The next steps include serious investment in supporting male victims of abuse, and in prevention of all childhood sexual abuse.